Human rights and the environment, Volume II - Shelton, Dinah; Sax, Joseph L. (Cheltenham, UK : Edward Elgar Publishing Limited, 2011)
In this topical collection, Professor Dinah Shelton brings together seminal articles published since the Stockholm Conference on the Human Environment that discuss and debate the linkages between human rights and environmental protection. This comprehensive two-volume set successfully encompasses the various approaches and thinking of the leading scholars in the field and is enhanced with an original introduction by the editor. This authoritative and timely book will be of great interest to lawyers, policy-makers, advocates and academics and will serve as an excellent reference tool for anyone with an interest in human rights and the environment.
Volume II. Indigenous Peoples and the Environment : Convergence from a Nordic Perspective / Lawrence Watters -- Indigenous Rights and the Environment : Evolving International Law / Cherie Metcalf -- Indigenous People and Environmental Justice : The Impact of Climate Change / Rebecca Tsosie -- The Protection of Environmentally-displaced Persons in International Law / Aurelie Lopez -- Sustaining the Environmental Rights of Children : An Exploratory Critique / Karen E. MacDonald -- In Pursuit of Environmental Human Rights : Commentary on the Draft Declaration of Principles on Human Rights and the Environment / t
Includes bibliographical references.
Keywords: Environmental law, International; Human rights; Environmental law, International; Human rights; Environmental law, International; Human rights